Identifikasi Dini Keterlambatan Bicara (Speech Delay) pada Anak Usia Dini melalui Interaksi di Kelas di TK IT Siti Khadijah - Khadijah Khadijah; Homsani Nasution; Dwi Nur Attira Ain; Nabila Nabila; Salsabila Wibowo; Sara Ningtya (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Early childhood represents a golden period that is vital for the development of all aspects of a child’s abilities, particularly language skills. Speaking ability plays a central role as it serves as a child’s primary means of communication and social interaction. However, not all children achieve speech milestones appropriate for their age. Speech delays can negatively affect social, emotional, and academic growth if not identified early. This study aims to identify speech delays in early childhood through classroom interactions and to analyze the role of teachers in early detection and stimulation of language skills. Using a descriptive qualitative approach, the study involved ten children aged 4–6 years at Siti Khadijah Kindergarten. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. Findings revealed that two children showed signs of speech delay, characterized by limited vocabulary, unclear pronunciation, and difficulty forming simple sentences. The main contributing factors were a lack of verbal stimulation at home and excessive gadget use, which reduced direct communication. Activities such as circle time, role-playing, and storytelling were found effective for detecting and stimulating speech development. Teachers play a crucial role as early detection agents, working collaboratively with parents to ensure continuous stimulation at home. Strengthening teachers’ capacity to observe, identify, and support children with speech delays is essential for promoting optimal language development.